A perturbation and generic smoothness of the Vafa-Witten moduli spaces on closed symplectic four-manifolds - Tanaka, Y (Cambridge University Press, 2018)
We prove a Freed{Uhlenbeck style generic smoothness theorem for the moduli space of solutions to the Vafa{Witten equations on a closed symplectic four-manifold by using a method developed by Feehan for the study of the PU(2)-monopole equations on smooth closed four-manifolds. We introduce a set of perturbation terms to the Vafa{ Witten equations, and prove that the moduli space of solutions to the perturbed Vafa{Witten equations on a closed symplectic four-manifold for the structure group SU(2) or SO(3) is a smooth manifold of dimension zero for a generic choice of the perturbation parameters.